The Meaning of Evaluation in Islamic Education - Dea Fitriyani; Lukmanul Hakim; Mitha Pebria Haerunnisa; Muhamad Rifaldi; Nenden Hayati; Maspuroh (Classroom: Journal of Islamic Education, 2025)
Evaluation of education in Islam holds profound and complex significance, encompassing spiritual, moral, and intellectual dimensions. This study aims to examine the principles of educational evaluation from an Islamic perspective and its impact on character development and student knowledge. In this context, evaluation is viewed not merely as a tool for measuring academic achievement but also as a process for shaping the ethical and spiritual dimensions of individuals. Through a qualitative approach, this research explores classical and contemporary texts on Islamic education, as well as the evaluative practices implemented in educational institutions. The findings indicate that evaluation grounded in Islamic values can enhance students' spiritual awareness, strengthen moral integrity, and promote holistic learning. Consequently, educational evaluation in Islam serves not only to assess learning outcomes but also to guide individuals toward higher life goals in accordance with religious teachings.